2011
DOI: 10.1111/j.1439-0485.2011.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical habitat and social conditions across a coral reef shape spatial patterns of intraspecific behavioral variation in a demersal fish

Abstract: As coral reef ecosystems decline in health worldwide, reef‐associated fishes are being impacted by changes to their coral reef habitats. While previous studies have shown coral reef structure to affect the demography of reef fishes, changes in reef conditions may also impact the behavior of reef fishes as they cope with altered habitats. In this study, we examined spatial patterns of intraspecific behavioral variation in the bicolor damselfish (Stegastes partitus) across the fringing reefs of Curaçao (Caribbea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…1). Schrandt et al (2011) identified distinct spatial patterns of intraspecific behavioral variation in bicolor damselfish associated with the occurrence of these 2 coral habitats at Playa Kalki. Transects (20 m in length and 3 m apart) were established on this fringing reef parallel to the shoreline, with 2 transects located in the rubble (depth range: 3.0 to 3.9 m) and 2 in live coral habitat (depth range: 5.8 to 7.9 m).…”
Section: Comparison Of Stress Reactivity In Bicolor Damselfish From Dmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Schrandt et al (2011) identified distinct spatial patterns of intraspecific behavioral variation in bicolor damselfish associated with the occurrence of these 2 coral habitats at Playa Kalki. Transects (20 m in length and 3 m apart) were established on this fringing reef parallel to the shoreline, with 2 transects located in the rubble (depth range: 3.0 to 3.9 m) and 2 in live coral habitat (depth range: 5.8 to 7.9 m).…”
Section: Comparison Of Stress Reactivity In Bicolor Damselfish From Dmentioning
confidence: 99%
“…Schrandt et al (2011) identified distinct patterns of association between intra specific behavioral variation in bicolor damselfish and variation in the coral reef environment. More specifically, large (> 4 cm total length [TL]) bicolor damselfish inhabiting shallow coral rubble areas exhibited higher rates of aggression, shelter use and courtship than bicolor damselfish in areas with higher coral cover nearer the reef slope (Schrandt et al 2011). Although this previous work revealed distinct relationships between coral reef characteristics and behavior in bicolor damselfish, the physiological bases for this behavioral variation have not been examined.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations